The rise of national socialism in the Bavarian Highlands a microhistory of Murnau, 1919-1933 - Raim, Edith 1965- (Microhistories, 2021)
List of FiguresAcknowledgementsAbbreviationsIntroductionChapter 1: Murnau at the Beginning of the Twentieth CenturyLife in MurnauPopulationClubs and societiesTourismChapter 2: Murnau During the Early Years of Crisis (1918/19-1923) Bavaria after 1918: politics in a state of emergencyRevolution and demobilizationParties and elections on local, regional and national levelsThe citizens' militiaEconomic crisis, plight and inflationLocal protagonists and völkisch propagandaAgitation against the Allies and reparationsThe Oberland LeagueAndreas Hofer LeagueThe founding of the National Socialist local branch in MurnauMembership in the NSDAP local branchCampaigning for the NSDAPHitler's visit to MurnauMurnau citizens participating in the Hitler PutschWar legacyReturning soldiers and death cultJames Loeb and the controversy about 'Jewish' moneySports and politicsWinter Sports ClubAviation as rearmament effort'Schützenvereine': marksmen's clubsWarriors' and Veterans' Association and League of Front FightersTourism and xenophobiaShrovetideCultural self-assertionChapter 3: Murnau during the Roaring Twenties (1924-1928)Tourism and politicsPoliticsThe Association for Germandom AbroadImposters and the bankruptcy and closure of businessesMass entertainment under völkisch rumblingRetail's struggle against consumer cooperativesInfrastructure and welfareChapter 4: Murnau and the Slide into Dictatorship (1929-1932)PropagandaCommunal, Landtag and Reichstag electionsMastering crisisThe Year 1930The year 1931The Murnau hospital. A perfect solution?Excursus: The trace of moneyThe year 1932ConclusionUnpublished SourcesArchivesPeriodicalsPublished SourcesPrimary sourcesSecondary sourcesIndex